Response of Broiler Chickens Fed a Combination of Cereal By-Products as Partial Replacement for Maize in their Diet - Tijjani, A.; Abdulsalam, I.; Audu, R.; Sadiq, M. S.; Salisu, I. B.; Dalha, M.; Rukayya, G. I. (Nigerian Journal of Animal Science and Technology (NJAST), 2019)
The experiment was conducted to investigate the response of Broiler chickens fed a combination of cereal by- products (maize offal, sorghum offal, and millet offal) as partial replacement for maize in their diet. A total of one hundred and twenty (120), seven- day old, unsexed broiler chickens were randomly divided into 4 treatments in a completely Randomized Design (CRD) with 30 birds per treatments, and replicated 3 times. The experimental diets were tagged T1(0:0:0) T2 ((2:1:1) T3, (1:2:1) and T4 (1:1:2). Feed and water were given ad libitum for three weeks with one-week adjustment period. The results revealed that all the parameters observed were significantly (p<0.05) different except for the initial weight which showed no significant (p>0.05) difference. Birds fed the control diet (0%cereal by-products) recorded the least value (99.74 g/b/d) in terms of feed intake, while final weight gain was significantly (p<0.05) higher (870.13g) for birds in treatment T4(1:1:2) but significantly (p<0.05) different from T1(780.40g) and T3 (828.40g). Daily and total weight gains were similar in T2, T3, and T4. Highest feed conversion ratio (FCR) was observed in T1. Cost of feed (naira per Kg), cost of feed consume (naira per day) and cost of feed per Kg weight gain was relatively higher in T1 (0% cereal by products) and lower for T2 (2:1:1) T3 (1:2:1) and T4 (1:1:2). It was therefore concluded that mixture of cereal by products (maize offal, sorghum offal, and millet offal) could replace some part of maize in a typical broiler’s ration for optimum performance and reduced cost.